Biomedical imaging : principles of radiography, tomography and medical physics - Salditt, Tim (De Gruyter graduate., 2017)
"While covering both physical and mathematical foundations, this graduate textbook provides the reader with a comprehensive introduction into modern biomedical imaging techniques. These methods are not only based on new instrumentation for image capture, but equally on mathematical advances in the algorithms to extract relevant information from recorded data. As a first, this book provides a combined treatise of these underlying aspects"--